Second Case of HOIP Deficiency Expands Clinical Features and Defines Inflammatory Transcriptome Regulated by LUBAC - Oda, Hirotsugu; Beck, David B.; Kuehn, Hye Sun; Sampaio Moura, Natalia; Hoffmann, Patrycja; Ibarra, Maria; Stoddard, Jennifer; Tsai, Wanxia Li; Gutierrez-Cruz, Gustavo; Gadina, Massimo; Rosenzweig, Sergio D.; Kastner, Daniel L.; et al. (Frontiers in Immunology, 2019)
Background: HOIP is the catalytic subunit of the linear ubiquitination chain assembly complex (LUBAC) that is essential for NF-κB signaling and thus proper innate and adaptive immunity. To date only one patient with HOIP deficiency has been reported with clinical characteristics that include autoinflammation, immunodeficiency, amylopectinosis, and systemic lymphangiectasia. Case: We sought to identify a genetic cause of a disease for an 8 year-old girl who presented with early-onset immune deficiency and autoinflammation. Methods: Targeted next generation sequencing of 352 immune-related genes was performed. Functional studies included transcriptome analysis, cytokine profiling, and protein analysis in patients’ primary cells. Results: We identified biallelic variants in close proximity to splice sites (c.1197G>C and c.1737+3A>G) in the RNF31 gene. RNA extracted from patient cells showed alternatively spliced transcripts not present in control cells. Protein expression of HOIP and LUBAC was reduced in primary cells as shown by western blotting. Patient-derived fibroblasts demonstrated attenuated IL-6 production, while PBMCs showed higher TNF production after stimulation with proinflammatory cytokines. RNA sequencing of whole blood RNA and PBMCs demonstrated a marked transcriptome wide change including differential expression of type I interferon regulated genes. Conclusion: We report the second case of HOIP deficiency with novel compound heterozygous mutations in RNF31 and distinct clinical and molecular features. Our results expand on the clinical spectrum of HOIP deficiency and molecular signatures associated with LUBAC deficiency.